INSTALASI PHOTO ELECTRIC SENSOR SEBAGAI PENUNJANG PENGEMBANGGAN SISTEM TRANSFER PNEUMATIC REAKTOR KARTINI BERBASIS PLC - Ananda Putra, Irvan; Haryo Sadewo, Prasetyo; Bismantolo, Putra (UNIB Press, 2025)
The installation of photoelectric sensors as a supporting element for the development of a pneumatic transfer system based on Programmable Logic Controller (PLC) in the Kartini Reactor aims to enhance efficiency and accuracy in operational processes. This study integrates photoelectric sensors to detect capsules in the pneumatic transfer system, which previously required manual intervention. The sensors send signals to the PLC, which controls actuators automatically. The system was optimized through installation, calibration, and testing, involving the measurement of capsule speeds for both empty capsules and those containing 3-gram samples. Results indicate significant operational efficiency improvements, with average transfer speeds of 12.41 m/s for empty capsules and 11.76 m/s for filled ones. This integration significantly contributes to advancing reactor automation systems based on PLC technology.